Soft power and national interest: evaluating the Islamic republic of Iran’s public diplomacy strategies - Bani Kamal, Abdol Moghset; Ra'ees, Wahabuddin Sahibuddin (IIUM Press, 2017)
This study investigates the role of ‘public diplomacy’ as an instrument of soft power in the Islamic Republic of Iran’s foreign policy in pursuit of its interests. It focuses on three public diplomacy institutions of Iran: al-Mustafa International University (MIU), Ahl-ul-bayt World Assembly (ABWA), and Imam Khomeini Relief Committee (IKRC). Adopting ‘relational public diplomacy’ approach, the book specifically focuses on building relations with elites, authorities, academics, and common people in Afghanistan and Malaysia through these public diplomacy institutions. The data have been collected from official documents and publications of these organizations, textual analysis of the statements of shia religious authorities and the Iranian leaders, particularly the founder of the Islamic Republic of Iran, late Ayatollah Khomeini, and his successor, Ayatollah Ali Khamenei, and fieldwork such as purposive interview. The book among others found that Iran is an ‘ideological sectarian state’ promoting shia version of Islamic values in different parts of the world including Malaysia and Afghanistan. These values are originating from the core shia principle of imamate. The nature of the public diplomacy activities of Iran in Malaysian and Afghanistan suggests that Iran’s foreign policy promotes the late Ayatollah Khomeini’s doctrine of ‘exporting revolution’. Evidences from Malaysian and Afghanistan reveal that Iran through its public diplomacy has been able to find supporters and sympathizers in the Muslim world who have developed close affinity with Iran. This Study recommends that the Muslim countries including Malaysia and Afghanistan need a comprehensive action plan to secure their societies from a sectarian tension resulting from the Islamic Republic of Iran’s sectarian oriented public diplomacy.